Response of Physalis peruviana L. genotypes to Fusarium oxysporum f. sp. physali under greenhouse - Pabón, Johana Elizabeth; Lagos-Burbano, Tulio César; Mejía-España, Diego Fernando; Duarte-Alvarado, David (Revista de Ciencias Agrícolas, 2022)
The goldenberry (Physalis peruviana) is an exotic fruit that in recent years has acquired great importance in both the local and international markets; one of the limiting phytosanitary problems for this crop is vascular wilt caused by Fusarium oxysporum f. sp. physali, which causes losses of 80-90%. The management of this pathogen is difficult and so far, it is based on preventive measures; however, there are alternatives such as genetic resistance, which is one of the most effective and profitable measures for its management. Taking that into account, the objective of this study was to evaluate the reaction of 40 genotypes of goldenberry against F. oxysporum under greenhouse conditions, by means of pathogenicity tests. The experiment was conducted in a selected place in the city of Pasto (Nariño department, south of Colombia). It was carried out with 40 genetic materials corresponding to different genotypes, one commercial control and four replicates per experimental unit; the statistical design was completely randomized. The traits evaluated were plant height (cm), disease severity (%), AUDPC area under the disease progress curve (units), disease incidence (%) and degree of vascular discoloration. The genotypes 09U138 and 12U399 have greater plant height (50.19 and 47.36 cm), lower AUDPC (zero units), lower incidence (0%) and lower degree of vascular discoloration (zero), with statistical differences from the rest of the genotypes, including the control. Field evaluations should be conducted with the same isolation and other commercial controls, as this research is only a step forward in the search for the resistance of uchuva to F. oxysporum.